On (f, g)-derivation in BCH-algebra - Sherly Afriastuti; Sri Gemawati; Syamsudhuha Syamsudhuha (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2021)
BCH-algebra is a non-empty set with the binary operation * and the constant 0, and statisfying the certain axioms. A mapping of d from X to itself is said to be a derivation in BCH-algebra if d is both (l, r)-derivation and (r, l)-derivation in BCH-algebra, where X is BCH-algebra. This article discusses the concepts of (l, r)-(f, g)-derivation, (r, l)-(f, g)-derivation, and (f, g)-derivation in BCH-algebra, and investigates the properties (l, r)-(f, g)-derivation, (r, l)-(f, g)-derivation and (f, g)-derivation in BCH-algebra.